2017
DOI: 10.1186/s40880-017-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic response after preoperative therapy predicts prognosis of Chinese colorectal cancer patients with liver metastases

Abstract: BackgroundPathologic response is evaluated according to the extent of tumor regression and is used to estimate the efficacy of preoperative treatment. Several studies have reported the association between the pathologic response and clinical outcomes of colorectal cancer patients with liver metastases who underwent hepatectomy. However, to date, no data from Chinese patients have been reported. In this study, we aimed to evaluate the association between the pathologic response to pre-hepatectomy chemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…In contrast, left‐sided tumours harbour chromosomal instability and CMS2 more often. Therapeutically, CRLMs from right‐sided primary tumours tend to have a lower response rate to preoperative chemotherapy than left‐sided tumours. On the other hand, although repeat hepatectomy has become a critical strategy for recurrent CRLM, patients with right‐sided tumours frequently experience disease recurrence with more advanced and unsalvageable disease, such as the presence of multiple recurrent lesions or EHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, left‐sided tumours harbour chromosomal instability and CMS2 more often. Therapeutically, CRLMs from right‐sided primary tumours tend to have a lower response rate to preoperative chemotherapy than left‐sided tumours. On the other hand, although repeat hepatectomy has become a critical strategy for recurrent CRLM, patients with right‐sided tumours frequently experience disease recurrence with more advanced and unsalvageable disease, such as the presence of multiple recurrent lesions or EHD.…”
Section: Discussionmentioning
confidence: 99%
“…Adam et al 30 Umeda et al 31 Huang et al 32 Mavros et al 33 Viganò et al 34 Connor et al 35 Eefsen et al 36 Schirripa et al 37 Norén et al 38 Sasaki et al 20 Shindoh et al 39 Amikura et al 40 Creasy et al 22 Dupré et al 41 Liang et al 43 Rhu et al 44 Sultana et al 45 Wang et al 46 Yamashita et al 21 Yamashita et al 21 Goto et al 47 Berardi et al 48 Cremolini et al 49 Engstrand et al 50 Goffredo et al 51 lmai et al 52 Koch et al 53 Laengle et al 54 Ledys et al 55 Liao et al 56 Lionti et al 57 Loosen et al 58 Makowiec et al 59 Margonis et al 60 Marques et al 24 Oshi et al 61 Palkovics et al 62 Shigematsu et al 63 Vallance et al 64 Wang et al 23 Wang et al 65 Zheng et al 66 Prediction interval 0·1 0 ·5 1 2 10…”
Section: Fig 2 Forest Plots Showing Impact Of Primary Tumour Locatiomentioning
confidence: 99%
See 1 more Smart Citation
“…These findings underline that considerable variations seem to exist in colorectal liver metastases and that its potential relationship to tumor response should not be neglected. Previous studies have confirmed that the tumor size, duration of perioperative chemotherapy, serum CEA level and preoperative chemotherapy regimens are efficient predictors of pathological response 19, 29. We speculate that tumor heterogeneity, manifesting differences in metastatic tumor burden and chemotherapy sensitivity, exists among liver metastases and results in pronounced discrepancies in TRG scores in the same patient after NACT.…”
Section: Discussionmentioning
confidence: 50%
“…Primary tumor location was also an important factor for chemotherapy response. Serayssol et al and Wang et al found that it was associated with poor pathologic response (11,12). However, other studies did not find similar results.…”
mentioning
confidence: 92%